Post-Heideggerian Drifts: From Object-Oriented-Ontology Worldlessness to Post-Nihilist Worldings - Segovia, Carlos A.; Gevorkyan, Sofya (Das Questões, 2020)
This paper rethinks the dynamics of what Heidegger called the modern Gestell ”“ i.e. dynamics behind the fulfilment of nihilism ”“ as that of an “unworlding” on whose subsequent “worldlessness” today’s Object-Oriented Ontology may be said to build. Also, it questions whether Heidegger’s early-Greek-oriented thought on being does not actually solicit an altogether different drift on the horizon of the possible, namely: that of thinking and re-experiencing dwelling in terms of retrieved “worldness.” Lastly, it reflects on the conditions of possibility that such dwelling, and its concomitant “worldings,” must meet, in dialogue with Heidegger, present-day animism studies, and non-religious Greek views on the sacred and the divine, in connection to which it articulates, and endorses, the concept of post-nihilism in contraposition to today’s nihilist philosophical wanderings.